Correlation of interleukin-6 and monocyte count to troponin I in acute coronary syndrome - Teguh Triyono Joni Parinding Usi Sukorini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Acute coronary syndrome (ACS) becomes an important disease, because of its increased prevalence and mortality rates. Makers of systemic inflammation, including interleukin-6 and monocyte count, have been shown to predict future cardiovascular events. However, the association between these inflammatory markers with cardiac injury is still a controversy.Objective: To evaluate the relationship between IL-6 and monocyte count as inflammation markers and troponin I as cardiac injury.Methods: This was a cross-sectional study. Subjects were patients suspected of ACS admitted to the emergency department of Sardjito Hospital Yogyakarta. Diagnoses were performed based on WHO criteria. Troponin I and interleukin-6 levels were measured from sera using sandwich ELISA method (Roche). Monocyte counts were determined by automatic hematology analyzer (Sysmex). Kruskal-Wallis test and Spearman's correlation test were used to assess the difference and correlation between parameters.Results: Sixty one (61) subjects were included in the study. Age of the subjects were 51-60 years, and diagnosed as ST elevation myocardial infarct (STEMI). Significant differences of IL-6 and troponin I levels were determined among unstable angina pectoris (UAP), non-ST elevation myocardial infarct (NSTEMI), and ST elevation myocardial infarct (STEMI) subjects. There was a moderate correlation (r = 0.54; p = 0.001) between troponin I and Interleukin-6, but not with monocyte count.Conclusion: Interleukin-6, but not monocyte count, was correlated with troponin I in acute coronary syndromes.Key words: acute coronary syndrome - interleukin-6 - monocyte count - troponin I